DAMPAK HILIRISASI NIKEL TERHADAP NILAI TAMBAH EKSPOR DANPERTUMBUHAN EKONOMI INDONESIA - Zulfikar Alkindi; Muhamad Rasya Al Rasyid; Dijan Rahajuni; Oki Anggraeni (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
Indonesia’s ban on raw nickel ore exports since January 2020has brought about significant structural changes to address the risks of the resource curse and commodity price volatility. This study analyzes the impact of the nickel downstream policy on the added value of Indonesian exports and economic growth. The method used is a descriptive quantitative approach, supported by qualitative analysis through document research. The data consist of secondary time series data for the period 2015–2024, which are analyzed using trend and comparative techniques (comparison of the period before downstreaming (2015–2019) and the period after (2020–2024)). The results show that downstreaming has succeeded in exponentially increasing the export value of nickel products (HS 75) to USD 8 billion in 2024 (a fivefold increase compared to 2015) and in bringing about a substantial increase in the export of iron and steel (HS 72). This policy has also triggered broad multiplier effects on the economy, as evidenced by investments of 13.8 billion dollar in the smelter sector, the creation of 120,000 new jobs, and an increase in non-tax state revenues. Despite the positive impact on post-pandemic GDP growth of more than 5%, implementation in the downstream sector still faces structural challenges, including the European Union lawsuit at the WTO, the dominance of Chinese investment, dependence on coal energy, and the limited mastery of advanced technologies by the local workforce, such as High-Pressure Acid leaching (HPAL). This study recommends the diversifying investments, accelerating the transition to green energy in the smelter sector, and strengthening domestic technology transfer.